Sensitivity to a Break in Interaural Correlation in Frequency-Gliding Noises - Fan, Langchen; Kong, Lingzhi; Li, Liang; Qu, Tianshu (Frontiers in Psychology, 2021)
This study was to investigate whether human listeners are able to detect a binaurally uncorrelated arbitrary noise fragment embedded in binaurally identical arbitrary-noise markers (a break in correlation, BIAC) in either frequency-constant (frequency-steady) or frequency-varied (unidirectionally frequency-gliding) noises. Ten participants with normal hearing were tested in Experiment 1 for up-gliding, down-gliding, and frequency-steady noises. Twenty-one participants with normal hearing were tested in Experiment 2a for both up-gliding and frequency-steady noises. Another nineteen participants with normal hearing were tested in Experiment 2b for both down-gliding and frequency-steady noises. Listeners were able to detect a BIAC in the frequency-steady noise (center frequency = 400 Hz) and two types of frequency-gliding noise (center frequency: between 100 and 1600 Hz). The duration threshold for detecting the BIAC in frequency-gliding noises was significantly longer than that in the frequency-steady noise (Experiment 1) and the longest interaural delay at which a duration-fixed BIAC (200 ms) in frequency-gliding noises could be detected was significantly shorter than that in the frequency-steady noise (Experiment 2). Although human listeners can detect a BIAC in frequency-gliding noises, their sensitivity to a BIAC in frequency-gliding noises is much lower than that in frequency-steady noise.